Gradual acquisition of visuospatial associative memory representations via the dorsal precuneus. Issue 5 (15th November 2018) - Schott, Björn H.; Wüstenberg, Torsten; Lücke, Eva; Pohl, Ina‐Maria; Richter, Anni; Seidenbecher, Constanze I.; Pollmann, Stefan; Kizilirmak, Jasmin M.; Richardson‐Klavehn, Alan
Abstract: Activation of parietal cortex structures like the precuneus is commonly observed during explicit memory retrieval, but the role of parietal cortices in encoding has only recently been appreciated and is still poorly understood. Considering the importance of the precuneus in human visual attention and imagery, we aimed to assess a potential role for the precuneus in the encoding of visuospatial representations into long‐term memory. We therefore investigated the acquisition of constant versus repeatedly shuffled configurations of icons on background images over five subsequent days in 32 young, healthy volunteers. Functional magnetic resonance imaging was conducted on Days 1, 2, and 5, and persistent memory traces were assessed by a delayed memory test after another 5 days. Constant compared to shuffled configurations were associated with significant improvement of position recognition from Day 1 to 5 and better delayed memory performance. Bilateral dorsal precuneus activations separated constant from shuffled configurations from Day 2 onward, and coactivation of the precuneus and hippocampus dissociated recognized and forgotten configurations, irrespective of condition. Furthermore, learning of constant configurations elicited increased functional coupling of the precuneus with dorsal and ventral visual stream structures. Our results identify the precuneus as a key brain structure in the acquisition of detailed visuospatial information by orchestrating a parieto–occipito–temporal network.